Analisis Du Pont System Untuk Mengukur Kinerja Keuangan Perusahaan Dalam Perspektif Islam: (Studi Pada Pt Midi Utama Indonesia Tbk (Alfamidi) - Siti Nurhafizah; Zuhrinal M. Nawawi; Kusmilawaty Kusmilawaty (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In analyzing the company's financial performance can be done using the Du Pont System method. Du Pont System is a chart designed to show the return on assets obtained from multiplying the profit margin by the total turnover of total assets. The purpose of this study was to determine the factors that caused the decline in financial performance using the Du Pont System method at PT Midi Utama Indonesia Tbk (Alfamidi). This research was conducted with qualitative descriptive analysis method. The object of this research is the audited financial statements of PT Midi Utama Indonesia Tbk (Alfamidi) for the period 2018 to 2022. Data collection was carried out using the documentation method. The data analysis technique used in this research is descriptive qualitative. The results of the analysis can be concluded that from the level of Net Profit Margin for five years, namely from 2018 to 2019 and from 2021 to 2022, it can be said that it has increased even though in 2020 there was a decrease and the company's performance is quite good because in these five periods the company has never experienced losses, from the level of Asset Turn Over for five years, namely from 2018 to 2019 and from 2021 to 2022